Parafermionic mapping of the two-colour delta model of interacting quarks - Daskaloyannis, C.; Bonatsos, Dennis; Kanakoglou, K. (HNPS Advances in Nuclear Physics, 2019)
Parafermions are used for creating an exact mapping of the two-colour delta model of interacting quarks, used in nuclear physics